Still's disease continuum from childhood to elderly: data from the international AIDA Network Still's disease registry - ALİBAZ ÖNER, FATMA (My University, 2023)
Objective Still’s disease is more frequently observed in the paediatric context, but a delayed onset is not exceptional both in the adulthood and in the elderly. However, whether paediatric-onset, adult-onset and elderly-onset Still’s disease represent expressions of the same disease continuum or different clinical entities is still a matter of controversy. The aim of this study is to search for any differences in demographic, clinical features and response to treatment between pediatric-onset, adultonset and elderly-onset Still’s disease. Methods Subjects included in this study were drawn from the International AutoInflammatory Disease Alliance Network registry for patients with Still’s disease. Results A total of 411 patients suffering from Still’s disease were enrolled; the disease occurred in the childhood in 65 (15.8%) patients, in the adult 314 (76.4%) patients and in the elderly in 32 (7.8%) patients. No statistically significant differences at post-hoc analysis were observed in demographic features of the disease between pediatric-onset, adult-onset and elderly-onset Still’s disease. The salmon-coloured skin rash (p=0.004), arthritis (p=0.009) and abdominal pain (p=0.007) resulted significantly more frequent among paediatric patients than in adult cases, while pleuritis (p=0.015) and arthralgia (p<0.0001) were significantly more frequent among elderly-onset patients compared with paediatric-onset subjects. Regarding laboratory data, thrombocytosis was significantly more frequent among paediatric patients onset compared with adult-onset subjects (p<0.0001), while thrombocytopenia was more frequent among elderlyonset patients although statistical significance was only bordered. No substantial differences were observed in the response to treatments. Conclusions Despite some minor difference between groups, overall, demographic, clinical, laboratory and treatments aspects of Still’s disease were similarly